Once Upon a Rhinoplasty: The History of the “Queen” of Facial Plastic Surgery - Adamson, Peter A.; Gantous, Andres (Facial Plastic Surgery, 2019)
The history of rhinoplasty is absolutely fascinating. It is replete with mysterious practices, intrigue, and imaginative thoughts. If necessity is the mother of invention, then sex, crimes, and punishment lay a legitimate claim to being the mother of rhinoplasty. The history of rhinoplasty is a global saga spanning the millennia. Practitioners of the art and science have included those demonstrating the most admirable traits espoused in the Hippocratic Oath, as well as those to whom the word “charlatan” might more aptly be applied. The truth of a story is illustrated in its telling, and we have attempted to be true historians. We recognize that observers and narrators, now well past (sic), have determined many of today's truths, and therefore their stories become our truths whether they were so or not. We have attempted to reference many who have contributed to the advance of this amazing surgical procedure, recognizing that we may have included some who have demonstrated marginal merit to be so. Assuredly, we have also unintentionally omitted some whom we should have included. From them we ask forbearance. Let the story begin, “Once upon a time…”
Keywords: rhinoplasty; external rhinoplasty; open rhinoplasty; closed rhinoplasty; endonasal rhinoplasty